MODERN APPROACHES TO THE TREATMENT OF HYPERCHOLESTEROLEMIA IN CORONARY HEART DISEASE PATIENTS WITH METABOLIC SYNDROME AND CHRONIC NON-ALCOHOLIC STEATOHEPATITIS - M. A. Osadchuk; L. I. Butorova; K. S. Solodenkova; G. M. Tokmulina (Российский кардиологический журнал)
Aim. To assess safety and effectiveness of combination therapy by simvastatin with ursodezoxycholic acid in treatment of dyslipidemia in coronary heart disease patients.Material and methods. Totally 30 CHD patients (stable angina, 2nd functional class — 2FC) having metabolic syndrome (MS) had combination therapy by simvastatin (20 mg/day) and ursodezoxycholic acid (Ursosan in daily dose 15 mg per kg) during 30 days. For all included patients the non-alcoholic steatohepatits (NASH) was confirmed. Of them 25 (85%) had clinical predictors of fibrosis and liver cirrhosis. All patients had abnormal bodyweight and arterial hypertension, very high risk of cardiovascular complications (CCC).Results. After 30 days of therapy there was sugnificant lowering of ALT from 83,61 (1,81, 5,49) to 51,32 (2,41, 5,76) МЕ/l, а AST — from 78,44 (2,02, 4,23) to 42,12 (1,99, 6,32) МЕ/l (mediana). In 7 patients levels of ALT and AST were normal. Also there was significant lowering of dyslipidemia: in 19 (63,3%) there was normalization of some lipid profile components, and in 9 (30%) we reached target LDL cholesterol 1,8 mmol/l. Also there was tendency to bodyweight normalization: BMI decreased by 1,28 kg/m2 in men and by 2,35 kg/m2 in women. During the study we did not find any significant side effects. All patients completed the course of simvastatin plus UDCA. Conclusion. Combination treatment by simvastatin and UDCA makes possible the achievement of lipid profile parameters significant improvement and the decrease of serum transaminase activity in patients with CHD and NASH. If not contraindicated, statins and UDCA can be recommended in CHD and non-alcoholic liver disease to reduce the risk of CCC.